Deep Phenotyping by Mass Cytometry and Single-Cell RNA-Sequencing Reveals LYN-Regulated Signaling Profiles Underlying Monocyte Subset Heterogeneity and Lifespan. Issue 10 (8th May 2020) - Roberts, Morgan E.; Barvalia, Maunish; Silva, Jessica A.F.D.; Cederberg, Rachel A.; Chu, William; Wong, Amanda; Tai, Daven C.; Chen, Sam; Matos, Israel; Priatel, John J.; Cullis, Pieter R.; Harder, Kenneth W.
Abstract : Rationale: Monocytes are key effectors of the mononuclear phagocyte system, playing critical roles in regulating tissue homeostasis and coordinating inflammatory reactions, including those involved in chronic inflammatory diseases such as atherosclerosis. Monocytes have traditionally been divided into 2 major subsets termed conventional monocytes and patrolling monocytes (pMo) but recent systems immunology approaches have identified marked heterogeneity within these cells, and much of what regulates monocyte population homeostasis remains unknown. We and others have previously identified LYN tyrosine kinase as a key negative regulator of myeloid cell biology; however, LYN's role in regulating specific monocyte subset homeostasis has not been investigated. Objective: We sought to comprehensively profile monocytes to elucidate the underlying heterogeneity within monocytes and dissect how Lyn deficiency affects monocyte subset composition, signaling, and gene expression. We further tested the biological significance of these findings in a model of atherosclerosis. Methods and Results: Mass cytometric analysis of monocyte subsets and signaling pathway activation patterns in conventional monocytes and pMos revealed distinct baseline signaling profiles and far greater heterogeneity than previously described. Lyn deficiency led to a selective expansion of pMos and alterations in specific signaling pathways within these cells, revealing a critical role for LYN in pMo physiology. LYN's role in regulating pMos was cell-intrinsic and correlated with an increased circulating half-life of Lyn -deficient pMos. Furthermore, single-cell RNA sequencing revealed marked perturbations in the gene expression profiles of Lyn −/− monocytes with upregulation of genes involved in pMo development, survival, and function. Lyn deficiency also led to a significant increase in aorta-associated pMos and protected Ldlr −/− mice from high-fat diet–induced atherosclerosis. Conclusions: Together our data identify LYN as a key regulator of pMo development and a potential therapeutic target in inflammatory diseases regulated by pMos. Abstract : Supplemental Digital Content is available in the text.